2022
DOI: 10.3390/technologies10060126
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Policy Framework Enabling Flexibility Markets—Bulgarian Case

Abstract: The legislation at the EU level is decisive in developing the local flexibility market. At the current stage, there are far-from-sufficient regulations on the local flexibility market, which can be perceived as a major barrier. The scope of this article is to explore the operational principles of the European local flexibility market and to assess the regulation of emerging flexible markets in order to help a new policy framework that facilitates the integration of flexible assets in the distribution grid. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The journal retracts the article "Policy Framework Enabling Flexibility Markets-Bulgarian Case" by Mladenov et al [1].…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The journal retracts the article "Policy Framework Enabling Flexibility Markets-Bulgarian Case" by Mladenov et al [1].…”
mentioning
confidence: 92%
“…Following publication, the authors contacted the editorial office regarding a number of scientific errors and concerns relating to the overall findings of this article [1]. Adhering to our complaints procedure, an investigation was conducted by the Editorial Office and the Editorial Board, which confirmed that several analytical errors occurred, specifically in the transfer of EU flexibility regulations and policy to the Bulgarian case, which is not currently supported or compatible within the actual state of the policy framework in this country, and therefore the findings could not be relied upon.…”
mentioning
confidence: 99%